2001
DOI: 10.1016/s0001-2092(06)61681-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction in Ambulatory Surgery

Abstract: The purpose of this study was to explore the relationships between patient satisfaction and selected variables that were identified as important in ambulatory surgery. The study addressed whether the selected variables are associated with the satisfaction of patients admitted to the hospital for ambulatory surgery. A descriptive correlational study was conducted in two hospital settings with 130 ambulatory surgical patients. Nurses (n = 16) in the ambulatory surgery departments completed a nurse demographic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Past studies have found that patients who had severe pain were significantly younger than those without it. [31][32][33] Other researchers have also found that patients undergoing orthopedic surgery related higher pain scores. Orthopedic patients have reported more pain and nausea at 72 hours than at any other earlier time period and required a continued need for nursing contact and support.…”
Section: Discussionmentioning
confidence: 96%
“…Past studies have found that patients who had severe pain were significantly younger than those without it. [31][32][33] Other researchers have also found that patients undergoing orthopedic surgery related higher pain scores. Orthopedic patients have reported more pain and nausea at 72 hours than at any other earlier time period and required a continued need for nursing contact and support.…”
Section: Discussionmentioning
confidence: 96%
“…Part of the nurse's role in the perioperative setting is to manage patient anxiety to support positive surgical outcomes and satisfaction with the surgical experience. 15 Anxiety triggers the stress response, stimulating the release of epinephrine and norepinephrine, which raises blood pressure and increases heart rate, cardiac output, and blood glucose levels. 3 Unfortunately, nurses and physicians have a fraction of the time they once had to achieve all of the postoperative goals and outcomes, including, but not limited to, pain management and postoperative education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The phenomenon of interest in this review is the patient subjective experience of perioperative care in the day surgery setting and how this relates to their subjective satisfaction with nursing care during this period. For the purpose of this review, subjective satisfaction from the patient perspective is seen as an indicator of quality patient care 10 …”
Section: Introductionmentioning
confidence: 99%